An Investigation on the level of communication and interaction in online learning programs / Noorriati Din ... [et. al.] - Din, Noorriati; Alwi, Mohd Rashidee; Haron, Shireen; Wee, Hassnah (2006)
Web-based distance education is a new and rapidly growing area of education in Malaysia. Universiti Teknologi MARA (UiTM), Universiti Tun Abdul Razak (UNITAR), and Universiti Putra Malaysia (UPM) are just a few of the higher learning institutions offering web-based distance education programs. This new mode of learning offers enticing advantages to adult learners giving them flexibility and autonomy over time, place, and the subject matter that they study. However, not every web-based distance learner experiences achievement with this new format. In fact, the dropout rates and failures in some programs are disturbingly high (Masculli, 2000).